2014
DOI: 10.1155/2014/972587
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tissue mRNA and Serum Antigen Levels of Members of the Urokinase-Type Plasminogen Activator System with Clinical and Prognostic Parameters in Prostate Cancer

Abstract: The objective was to determine the mRNA expression and protein levels of uPA system components in tissue specimens and serum samples, respectively, from prostate cancer (PCa) patients and to assess their association with clinicopathological parameters and overall survival (OS). The mRNA expression levels of uPA, its receptor (uPAR), and its inhibitor type 1 (PAI-1) were analyzed in corresponding malignant and adjacent nonmalignant tissue specimens from 132 PCa patients by quantitative PCR. Preoperative serum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
(66 reference statements)
3
14
0
Order By: Relevance
“…]). Recently, we showed in an independent PCa patient cohort that high suPAR protein levels in the serum were associated with a sevenfold increased risk of death compared with patients with low/intermediate levels . Our results confirmed previous findings of a significant association between elevated suPAR levels in blood and a poor outcome .…”
supporting
confidence: 90%
“…]). Recently, we showed in an independent PCa patient cohort that high suPAR protein levels in the serum were associated with a sevenfold increased risk of death compared with patients with low/intermediate levels . Our results confirmed previous findings of a significant association between elevated suPAR levels in blood and a poor outcome .…”
supporting
confidence: 90%
“…Riddick et al [28] used qPCR and found increased mRNA expression in malignant tissue samples from patients with PC compared to non-malignant samples from patients with benign prostatic hyperplasia with statistically significant positive correlations with Gleason score. However, this could not be confirmed in the study by Al-Jabani et al [27], where increased mRNA expression levels of uPA and PAI-1 and not uPAR were found in PC tissue compared to benign prostate hyperplasia and normal prostate tissue.…”
Section: Upar and Prostate Cancermentioning
confidence: 72%
“…Similar to the immunohistochemical analysis, uPAR expression at mRNA level has only been investigated in a limited number of studies and only in small populations of PC patients, using either in situ hybridization or real-time quantitative PCR (qPCR) [22, 23, 27, 28]. Riddick et al [28] used qPCR and found increased mRNA expression in malignant tissue samples from patients with PC compared to non-malignant samples from patients with benign prostatic hyperplasia with statistically significant positive correlations with Gleason score.…”
Section: Upar and Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…48,6266 Increased expression of uPAR has been associated with more aggressive and advanced CaP relative to indolent or localized disease. 63,6771 Developing uPAR-targeted analogs labeled with SPECT radionuclides would be desirable to aid CaP assessment in patients. In the present study, the 99m Tc-labeled AE015 peptide was utilized in binding assays in vitro with PC-3 cells and in biodistribution analyses in vivo with mice bearing PC-3 xenografts.…”
Section: Introductionmentioning
confidence: 99%